On a class of Lyapunov's inequality involving $ λ $-Hilfer Hadamard fractional derivative - Lakhdar Ragoub; J. F. Gómez-Aguilar; Eduardo Pérez-Careta; Dumitru Baleanu (AIMS Mathematics, 2024)
In this paper, we presented and proved a general Lyapunov's inequality for a class of fractional boundary problems (FBPs) involving a new fractional derivative, named $ λ $-Hilfer. We proved a criterion of existence which extended that of Lyapunov concerning the ordinary case. We used this criterion to solve the fractional differential equation (FDE) subject to the Dirichlet boundary conditions. In order to do so, we invoked some properties and essential results of $ λ $-Hilfer fractional boundary value problem (HFBVP). This result also retrieved all previous Lyapunov-type inequalities for different types of boundary conditions as mixed. The order that we considered here only focused on $ 1 < r≤ 2 $. General Hartman-Wintner-type inequalities were also investigated. We presented an example in order to provide an application of this result.